Smartphone ownership and usage in Chinese‐ and English‐speaking older adults. (31st December 2021) - Li, Clara; Zeng, Xiaoyi; Wang, Kun; Neugroschl, Judith A.; Aloysi, Amy; Cai, Dongming; Martin, Jane; Sewell, Margaret; Greenberg, Jonathan; Xu, Mengfei; Evans, Kirsten; Pun, Kelly; et al.
Abstract: Background: Data collection by smartphone is becoming more widespread in healthcare research. Previous studies reported racial/ethnical differences in the use of digital health technology. However, cross‐language group comparison (Chinese‐ and English‐speaking older adults) were not performed in these studies. This project will expand to smartphone technology use in diverse older populations with a focus on Chinese American older adults who are monolingual Chinese‐speakers. Method: The Alzheimer's Disease Research Center (ADRC) at Icahn School of Medicine at Mount Sinai (ISMMS) evaluates diverse older populations using National Alzheimer's Coordinating Center's Uniform Data Set (NACC UDS). The UDS has different language versions, including English and Chinese. The evaluation includes a medical examination, cognitive assessments, and a research blood draw. Smartphone ownership and usage were captured using a local questionnaire developed by our ADRC. The questionnaire, available in English and Chinese, was administered by our ADRC coordinators during the COVID‐19 pandemic. Multivariate analysis of variance (MANOVA) was used to examine differences in technology ownership and usages between the two language groups, while controlling for age, gender, education, and cognitive status (measured by Clinical Dementia Rating). Result: 33 Chinese‐ and 117 English‐speaking older adults who received a diagnosis of normal cognition or mild cognitive impairment at consensus were included in the data analysis. Results reveal a high prevalence of smartphone ownership in our Chinese‐ (100%) and English‐speaking older participants (86.3%). Participants in both language groups use mobile technology for a wide range of purposes, such as getting news and other information (Chinese=90.9%; English=87.2%), sending/receiving text (Chinese=97.0%; English=96.6%), watching videos/TV shows (Chinese=78.8%; English=69.2%), and taking classes (Chinese=57.5%; English=57.3%). However, Chinese‐speaking older adults were less likely than English‐speaking older adults to use mobile technology to post their own reviews or comments online (Chinese=9.1%; English=39.3%, p=0.001), download or purchase an app (Chinese=21.2%; English=70.9%, p<0.001), track health/ fitness via apps/website (Chinese=12.1%; English=47.9%, p<0.001) and manage/receive medical care (Chinese=15.2%; English=67.5%, p<0.001). Conclusion: Our findings highlight potential barriers to smartphone usage in Chinese American older adults with limited English proficiency. The results have implications for how smartphone technology can be used in clinical practice and aging research.